The Comparison Between Balinese and South Korean Swear Words in Terms of References Used - Suari, Ni Putu Pradnya; Budasi, I Gede; Sari, Rima Andriani (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
The objective of this research is to compare the references in swear words in South Korean and Balinese. A comparative descriptive qualitative research design with document analysis was employed in this study. The data for this study were gathered from previous studies, which focused on Balinese swear words in informal Standard Korean (Pyojuneo) and Balinese language spoken in Buleleng regency. The findings show that both Balinese and South Korean swear words share several similar reference domains, including sexual activities, excretion, religion or supernatural beings, social conditions, concrete objects, abstract concepts or situations, body parts, animals, actions, and professions. Although Balinese swear words tend to refer more to animals, mythical beings, and personal characteristics based on local cultural beliefs, South Korean swear words tend to have more varied expressions referring to sexual behavior and personal attacks. The findings of this study indicate that although the two languages share common taboo domains of reference, the cultural interpretations and sensitivities of these references differ, as do the sociocultural norms of South Korean and Balinese societies. In conclusion, understanding the similarities and differences in references between Balinese and South Korean languages can help speakers avoid misinterpretation in communication.